2006
DOI: 10.1634/stemcells.2005-0508
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Extracellular Matrix During Chondrogenic Differentiation of Mesenchymal Stem Cells Correlates with Increased Levels of Xylosyltransferase I

Abstract: In vitro differentiation of mesenchymal stem cells (MSCs) into chondrogenic cells and their transplantation is promising as 1,4-N-acetylgalactosaminyltransferase), and GlcAC5E (glucuronyl C5 epimerase). All key enzymes showed a similar regulation with temporarily downregulated mRNA levels (up to ؊87-fold) after chondrogenic induction. In accordance to previous studies, we observed a similar increase in the expression of PG core proteins. In conclusion, we could show that key enzymes for CS, DS, and HS synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…FAM20B is reportedly a Xyl kinase that regulates GAG biosynthesis (5) and controls the timing of endochondral ossification by inhibiting chondrocyte maturation (32). In addition, the expression level of EXTL2 reportedly increases during chondrogenesis (34). Based on these findings, we propose that EXTL2 plays an important role in the regulation of GAG synthesis in concert with FAM20B and that an imbalance between EXTL2 and FAM20B functions may lead to abnormal endochondral ossification.…”
Section: Discussionmentioning
confidence: 91%
“…FAM20B is reportedly a Xyl kinase that regulates GAG biosynthesis (5) and controls the timing of endochondral ossification by inhibiting chondrocyte maturation (32). In addition, the expression level of EXTL2 reportedly increases during chondrogenesis (34). Based on these findings, we propose that EXTL2 plays an important role in the regulation of GAG synthesis in concert with FAM20B and that an imbalance between EXTL2 and FAM20B functions may lead to abnormal endochondral ossification.…”
Section: Discussionmentioning
confidence: 91%
“…Fourteen days after induction, the cell pellets were xed with 4% paraformaldehyde, embedded in paraf n and cut into 5 μm sections [15]. Sections were stained with 1% toluidine blue (Sigma, USA) at pH 2.5 for 30 min and rinsed with tap water.…”
Section: Induction Of Multilineage Differentiationmentioning
confidence: 99%
“…The promoters of the xylosyltransferase genes have not yet been characterized, and therefore cell-typespecific transcriptional response elements are not yet identified. However, it has been shown that both xylosyltransferase genes are differentially regulated during transforming growth factor (TGF) b 3 -induced chondrogenic differentiation of mesenchymal stem cells [59]. XT-I is the predominant xylosyltransferase in the early phase of chondrogenic stem cell differentiation and XT-II is upregulated 7 days after induction.…”
Section: Tissue-specific Expression Of Xt-i and Xt-iimentioning
confidence: 99%
“…Until now, the amino acids in the xylosyltransferase stem regions where the proteolytic cleavage occurs have not been identified. Xylosyltransferase secretion seems to be independent of cell type and organ system, as xylosyltransferase activity has been identified in culture supernatants of all cell lines investigated [42,59,87] and in many human body fluids, including blood, synovial fluid, semen, follicular fluid and liquor cerebrospinalis [28, 42, 87, 96 -99]. Until now, no UDP-xylose has been found in the extracellular space, indicating that no xylosyltransferasemediated xylose transfer to protein substrates occurs due to the lack of donor substrates.…”
Section: Secretion Of Xt-i and Xt-ii Into Extracellular Spacementioning
confidence: 99%
See 1 more Smart Citation